"Chimurenga" 1896-1897: a revisionist study - Horn, Mark Philip Malcolm (Rhodes University, Faculty of Humanities, Department of History, 1987)
There were no "Rebellions" in 1896-7. The concept of "risings" which is to be found in the European perspective of the escalated violence has distorted an understanding of the complex nature of the events. The events of 1896-7 must rather be explained through an examination of the details of the conflict. European pressure on the African people prior to 1896 was minimal and cannot be assumed to be the "cause" of the first "Chimurenga". There was no planned, organised or coordinated "rebellion" in Matabeleland in March 1896. Further, no distinction can be made between a "March" rebellion in Matabeleland and a June "rebellion" in Mashonaland. A European war of conquest in 1896-7 evoked the responce known now as the first "Chimurenga". It was the war of conquest of 1896-7 which saw the ascendancy of the European perspective over the African and thereby established the psychological foundations of the Rhodesian colonial state. The complex nature of the events of 1896-7 is to be understood through an appreciation of the different perspectives of those who became embroiled in the conflict.
Keywords: National liberation movements -- Zimbabwe; Political violence -- Zimbabwe; Zimbabwe -- Politics and government -- 1980-; Zimbabwe -- History -- Chimurenga War, 1966-1980